Application Marketing Strategy Using Social Media in the Technology Industry: A Case Study of Gojek, Medan City - Wirayuda Nasution; Solihah Titin Sumanti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to analyze application marketing strategies using social media in the technology industry: a case study of Gojek, Medan City. Gojek has been operating in the city of Medan, which is the capital of North Sumatra Province, Indonesia. With the presence of Gojek in Medan, people can enjoy the various services offered by this company. It's just that Gojek's success in the city of Medan cannot be obtained without a marketing strategy using social media. Therefore, to analyze it using descriptive qualitative research methods. Data collection is done by means of observation, interviews, document analysis, literature study. The results of the study show that advertisements issued by Gojek in the city of Medan utilize social media such as Instagram, Youtube, Twitter, TikTok, Facebook and others. Big ideas that are unique and innovative, then able to be broken down in more detail. There are five strategies for Gojek in Medan City in utilizing social media, namely: 1) Visual and storytelling with an attractive composition; 2) Using continuity in everyday life; 3) The right location for ad placement (both offline and online media); 4) Demographic analysis of specific target markets.